VALIDATION OF E-MODULES ON CHEMICAL MATERIALS AROUND US USING A SYSTEM THINKING APPROACH IN THE CONTEXT OF THE SEBATIK ISLANDS - Rabiatul Adawiyah; Amadou F. Jellow; Asih Widi Wisudawati (JCER (Journal of Chemistry Education Research), 2025)
As an island region on the outer edge of Indonesia, learning processes on Sebatik Island require learning materials that improve students’ system thinking skills, which contain the abilities to identify parts of systems and their interactions, identify cause and effect, organise their relationships among parts of systems, and hold ownership for their environment. According to those significant abilities for Sebatik’s students, this study aims to develop a systems thinking-based e-module on environmental chemistry that aligns with the contextual characteristics of Sebatik Island. With the availability of learning media in the form of system thinking-based e-modules on environmental chemistry, it is hoped that students' understanding of contextual chemistry in accordance with the nature of Sebatik Island will improve. This study applies the Research and Development (R&D) method by adopting the development stages in the ADDIE model, focusing on the development and validation of a newly developed e-module. However, this research focuses on the development stage, taking into account the conditions of the region and the time frame of the research. 10th-grade MIPA students from SMA/MA participated in providing feedback on the e-module through student response sheets,this module has been validated by subject matter and media experts and evaluated by teachers to assess its suitability and effectiveness. The validation results show that the subject matter aspect achieved a score of 98.6% (very good), the media aspect 86.7% (very good), and the teacher's assessment 93.33% (very good). Student responses were also positive, with a percentage of 97.3% (very good). Based on these results, the system thinking-based e-module developed is suitable for use as an alternative learning medium, capable of facilitating holistic conceptual understanding, and relevant to the context of students' daily lives.